Trazodone and Omeprazole Interaction causing Frequent Second-Degree Mobitz Type 1 Atrioventricular (AV) Block (Wenckebach Phenomenon) and Syncope: A Case Report and Literature Review - Akinseye, Oluwaseun A. (Am J Case Rep, 2015)
Patient: Male, 54 Final Diagnosis: Trazodone and omeprazole interaction causing second-degree Mobitz type 1 AV block and syncope Symptoms: Syncope Medication: — Clinical Procedure: Trazodone and omeprazole withheld Specialty: Cardiology OBJECTIVE: Unexpected drug reaction BACKGROUND: This case report highlights serious cardiovascular adverse effects with a conventional dose of trazodone as a result of its potential interaction with omeprazole. CASE REPORT: A 54-year-old man who was a former smoker, with dyslipidemia, coronary artery disease, and anxiety disorder developed lightheadedness and syncope the morning of admission. He was taking trazodone 50 mg daily, omeprazole 20 mg daily, and simvastatin 20 mg at bedtime. He doubled the dose of trazodone 50 mg on the night prior to presentation to calm his anxiety. An electrocardiogram revealed sinus rhythm at 60 beats per minute and second-degree Mobitz type 1 atrioventricular (AV) block with 5:4 AV conduction. Results of basic metabolic panel, thyroid-stimulating hormone, and chest radiograph were normal. A transthoracic echocardiogram revealed aortic valve sclerosis. We tested for Lyme disease given his history of hunting in the woods 8 months prior to presentation, but the titer was negative. Trazodone and omeprazole were discontinued. By the 3(rd) day of medication discontinuation, all symptoms had resolved and the frequency of second-degree AV Mobitz type 1 AV block had decreased to once per hour. CONCLUSIONS: Due diligence and meticulous attention to detail needs to be exercised to uncover drug interactions as potential causes of lethal and nonlethal patient symptomatology, as in this case of syncope caused by concomitant use of trazodone and a widely prescribed medication, omeprazole.